Infeksi Organ Berdekatan Yang Cepat Menyebabkan Selulitis Orbital Pada Pasien Imunokompromais: Laporan Kasus - Annisa Ayu Rachmawati (Yayasan Pendidikan Medika Indonesia, 2023)
Introduction: Orbital cellulitis (OC) is a vision-threatening condition caused by an infection of the tissue behind the orbital septum. It can easily occur, especially when the individual's condition is accompanied by a weakness of the normal host defenses or because of hypervirulence of the causative microbe. Patients with comorbid or underlying conditions, may have higher risk. If left untreated, OC can seriously result in vision loss and life-threatening conditions. Case report: We reported a 46-year-old untreated diabetic male came to the ER with unilateral right eye pain, proptosis and oedema of the infected eye, headache, also fever. A diagnosis of OC with several comorbidities such as diabetic mellitus, and reactive anti-HIV was made. The diagnosis was also suspected by his condition before the symptoms, odonto-sinusitis that could be a primary infection of his right OC. A culture examination of the pus found coccus, Gram positive. The patient was admitted for seven days. However, the patient had died when outpatient schedule control. Conclusion: This complex case demonstrates the importance of a multidisciplinary approach to the management of OC starting from the risk factors present to prevent serious complications and permanent sequelae. Immunocompromised condition in our patient may have contributed his rapid deterioration.